Uji Sifat Campuran Herbisida Berbahan Aktif 2,4-D Dimetil Amina+Isopropilamina Glifosat terhadap Gulma Ottochloa nodosa, Cyperus rotundus, dan Praxelis clematidea - Ardan Maulana; Herry Susanto; Hidayat Pujisiswanto; Nanik Sriyani (Jurnal Penelitian Pertanian Terapan, 2023)
Chemical weed control in cultivated plants generally uses one herbicide active ingredient, but its effectiveness in controlling weeds can be increased by mixing herbicides. Mixing of more than 1 active ingredient can be additive, synergistic, and antagonistic with other active ingredients. Therefore, it is necessary to study the combination of herbicide active ingredients that will be used. The aim of the study was to determine the herbicide properties of a mixed 2,4-D dimethyl amine + Isopropylamine Glyphosate applied to the weeds Ottochloa nodosa, Cyperus rotundus, and Praxelis clematidea whether additive, synergistic, or antagonistic. The research was carried out from December 2020 to February 2021, at the Integrated Field Greenhouse and Weed Science Laboratory, Faculty of Agriculture, University of Lampung. Using a Randomized Block Experiment Design (RAK) with treatment consisting of the herbicide Goldenstar with a single active ingredient 2,4- D dimethyl amine 100g/l with doses of active ingredients consisting of 25, 50, 100, and 200 g/ha, Isopropylamine Glyphosate 300 g/l with doses of active ingredients consisting of 75, 150, 300, and 600, g/ha and herbicides Goldenstar active ingredient mixture of 2,4-D dimethyl Amine + Isopropylamine Glyphosate 100/300 g/l with a dose of active ingredients consisting of 50, 100, 200, and 400 g/ha and control treatment (without herbicides). The target weeds included Otthocloa nososa, Cyperus rotundus, and Praxelis clematidea. Analysis to test the nature of herbicide mixture using the MSM (Multiplicative Survival Model) test. Furthermore, the co-toxicity value was calculated by comparing the expected LD50 and treatment LD50 values. The results showed that mixing herbicide with the active ingredient 2,4-D dimethyl Amine + Isopropylamine Glyphosate 100/300 g/l on the dry weight accumulation of the weeds Ottochloa nodosa, Cyperus rotundus, and Praxelis clematidea had an LD50 of 1.8424 g/ha and an LD50 of treatment. The expectation is 4.8270 g/ha with a co-toxicity value of 2.6 (co-toxicity value > 1) so that the herbicide mixture with the active ingredient 2,4-D dimethyl Amine + Isopropylamine Glyphosate 100/300 g/l is synergistic. . Keywords : 2,4-D dimethyl amine, Isopropylamine glyphosate, LD50, MSM (Multiplicative Survival Model)